2000
DOI: 10.2307/3284882
|View full text |Cite
|
Sign up to set email alerts
|

Skin Lesions Caused by Dermophthirius penneri (Monogenea: Microbothriidae) on Wild-Caught Blacktip Sharks (Carcharhinus limbatus)

Abstract: Skin lesions caused by the ectoparasite Dermophthirius penneri Benz, 1987 (Monogenea: Microbothriidae) on 2 wild-caught blacktip sharks (Carcharhinus limbatus) from the northern Gulf of Mexico were studied using light and scanning electron microscopy. Grossly, lesions appeared as multifocal, well-demarcated, ovoid or irregularly shaped, light gray patches of skin. Scanning electron microscopy of lesions revealed gaps between placoid scales apparently created by detachment and loss of placoid scales, rotated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…There were occasionally patches of bluish discoloration on host skin with apparent scale loss (determined by gross visual and tactile examination). These were anecdotally associated with relatively intense infections by Dermophthirioides pristidis and (Poynton et al 1997, Bullard et al 2000, Young et al 2013. Occasionally, smalltooth sawfish specimens presented with lesions associated with a single specimen each of the leech Branchellion torpedinis Savigny, 1822.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were occasionally patches of bluish discoloration on host skin with apparent scale loss (determined by gross visual and tactile examination). These were anecdotally associated with relatively intense infections by Dermophthirioides pristidis and (Poynton et al 1997, Bullard et al 2000, Young et al 2013. Occasionally, smalltooth sawfish specimens presented with lesions associated with a single specimen each of the leech Branchellion torpedinis Savigny, 1822.…”
Section: Resultsmentioning
confidence: 99%
“…The bluish patches of skin sometimes associated with infections by Dermophthirioides pristidis in our samples are similar to those caused by its relative Dermopthirius penneri Benz, 1987 on the skin of the blacktip shark Carcharhinus limbatus (Müller & Henle, 1839). Bullard et al (2000) described these lesions in detail and concluded that they were not severe or debilitating unless environmental conditions were such that the parasite popu- 4 400 µm 00 µm Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…Given the seemingly limited number of possibilities for what tissue, extracellular components, or whole cells that these capsalines may feed upon, we speculate that the majority of their diet comprises components of the epidermis, e.g., malpighian cells and goblet cells. As indicated for other monogenoids that infect fish skin [53], specimens of C. cf. biparasiticum would thereby gain access to a continuous source of regenerating host cells at their attachment site.…”
Section: Parasite-host Relationshipmentioning
confidence: 99%
“…The same species of worm occurred in lower intensity and produced relatively minor lesions in wild shark individuals investigated (Bullard et al 2001). The same authors (Bullard et al 2000a) also studied skin lesions caused by the microbothriid Dermophthirius penneri on the wild blacktip shark, Carcharhinus limbatus. Lesions appeared as multifocal, well-demarcated, light gray patches on the skin, but they were chronic conditions not associated with secondary bacterial infections or any debilitating disease.…”
Section: Helminth (Worm) Parasitesmentioning
confidence: 99%